Implementation of the Discount Policy on the Cost of Adding Electricity and Its Impact on the Level of Household Energy Consumption at PLN (Persero) UP 3 Dumai - Ade Rahmat Putra; Trio Saputra; Surya Dailiati (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study aims to analyze the implementation of the discount policy on the cost of adding electricity and its impact on household energy consumption at PLN (Persero) UP3 Dumai. The research uses a mixed method approach by combining quantitative and qualitative data. The population in this study is all PLN UP3 Dumai customers, with a sample in the form of customers who added electricity during the January-December 2025 period. The sampling technique uses purposive sampling. Quantitative data was obtained through documentation of customer data on power increases at normal and discounted prices, while qualitative data was obtained through interviews with the Head Manager of PLN UP3 Dumai and the Assistant Manager for Commerce and Marketing, as well as customers who only pay normal prices and take advantage of discount programs. Quantitative data analysis used the Shapiro-Wilk normality test and the Independent sample t-test, while qualitative data were analyzed through data reduction, presentation, and conclusion drawn. The results of the study showed that the discount policy was able to increase the number of customers who added power, especially during the promo period, but did not have a significant effect on household electrical energy consumption (Sig. = 0.610 > 0.05). In conclusion, discount policies are more effective as a stimulus to increase access and capacity of electricity than as a driver of increased energy consumption. Further research is recommended to examine socioeconomic factors and actual energy consumption data in the long term.